Linking research to practice: the landscape as the basis for integrating social and ecological perspectives of the rural - Pinto-Correia, Teresa (2014)
The rural spaces in Europe are undergoing complex processes of transition, at multiple scales, and rhythms. In order to grasp and understand the changes occurring, the need emerges for new, conceptual approaches that make it possible to combine the different factors that shape spaces. Recent, literature on the multifunctional character of rural spaces and their transition pathways shows the, need for spatially based approaches, where the natural characteristics of a landscape are combined, with the socio-economic and cultural drivers that affect its changes. Experience shows how practical, questions on the changes affecting the rural, addressed by society to the scientific community, are of a, new character and require novel research approaches. This paper argues that landscape based, approaches can be useful basis for the required conceptual innovation. The paper presents and, discusses a set of examples of practice driven research developments, in contrasting regions of Europe. And it proposes a conceptual model which aims to contextualize empirical research driven by, problems set up in practice, and combining the ecological and structural dimensions with the socioeconomic, and cultural ones, all converging in the rural landscape, at multiple scales. The landscape, as, the spatial entity, in its material and immaterial dimensions, is presented in this paper as the most, comprehensive basis for the required step forward. This does not mean a disciplinary landscape, analysis revisited, but a new multi-scale and multi-domain place based approach, where the place is, the rural landscape.